2009
DOI: 10.1007/s00705-009-0509-3
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of four RNA segments of fig mosaic virus

Abstract: The complete sequence of four viral RNA segments of fig mosaic virus (FMV) was determined. Each of the four RNAs comprises a single open reading frame (ORF) 7,093, 2,252, 1,490 and 1,472 nucleotides in size, respectively. These ORFs encode the following proteins in the order: RNA-dependent RNA polymerase (p1 264 kDa), a putative glycoprotein (p2 73 kDa), a putative nucleocapsid protein (p3 35 kDa) and a protein with unknown function (p4 40.5 kDa). All RNA segments possess untranslated regions containing at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 27 publications
7
96
0
Order By: Relevance
“…Comparison of the nucleotides and predicted amino acid sequence of all RNA segments of Emaravirus-like viruses with their homologue showed that RNA1 is the most conserved segments among all others analyzed, for which that of FMV, EMARaV, RLBV, RRV and RYRV revealed the presence of five highly conserved regions denoted as motifs (A-E) in the RdRp gene, similarly to what has been previously reported with FMV and EMARaV by Elbeaino et al, (2009aElbeaino et al, ( , 2009b. Computer-assisted analysis showed that among all five analyzed regions, the pre-motif A, motifs A and C were the most conserved ones (data not shown) (Fig.…”
Section: Design Of Oligonucleotide Degenerate Primers For Emaravirus-supporting
confidence: 78%
See 3 more Smart Citations
“…Comparison of the nucleotides and predicted amino acid sequence of all RNA segments of Emaravirus-like viruses with their homologue showed that RNA1 is the most conserved segments among all others analyzed, for which that of FMV, EMARaV, RLBV, RRV and RYRV revealed the presence of five highly conserved regions denoted as motifs (A-E) in the RdRp gene, similarly to what has been previously reported with FMV and EMARaV by Elbeaino et al, (2009aElbeaino et al, ( , 2009b. Computer-assisted analysis showed that among all five analyzed regions, the pre-motif A, motifs A and C were the most conserved ones (data not shown) (Fig.…”
Section: Design Of Oligonucleotide Degenerate Primers For Emaravirus-supporting
confidence: 78%
“…The genus deems its' acronym to the European mountain ash ringspot-associated virus (EMARaV), firstly identified and is the type species of this genus, which has a genome composed of four RNA segments (Mielke and Muehlbach, 2007). Fig mosaic virus (FMV) is an another approved species (Adams and Carstens, 2012) of the recently established genus Emaravirus with a genome composed of six single-stranded negative-sense RNA that has recently been recognised as the causal agent of fig mosaic disease (FMD) (Elbeaino et al, 2009a;2009b. Intracellular DMBs were identified as particles of the putative causal agents of fig mosaic and of the ringspot disease of European mountain ash (Mielke and Muehlbach, 2007;Elbeaino et al, 2009a;2009b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, EMARAV and rose rosette virus (RRV) are reported to have four genomic RNA segments (Mielke & Muehlbach, 2007;Laney et al, 2011). Fig mosaic virus (FMV) was initially reported also to have four RNAs, which have now been supplemented by another two (Elbeaino et al, 2009;Ishikawa et al, 2012). RLBV was reported initially to have five RNA segments but is now known to have at least eight (McGavin et al, 2012;S.…”
Section: Introductionmentioning
confidence: 99%